Friends, strangers, and bystanders: Informal practices of sexual assault intervention. Issue 1 (2nd January 2019) - Wamboldt, Alexander; Khan, Shamus R.; Mellins, Claude Ann; Hirsch, Jennifer S.
ABSTRACT: Sexual assault is a part of many students' experiences in higher education. In U.S. universities, one in four women and one in ten men report being sexually assaulted before graduation. Bystander training programmes have been shown to modestly reduce campus sexual assault. Like all public health interventions, however, they have unintended social consequences; this research examines how undergraduate men on one campus understand bystander interventions and how those understandings shape their actual practices. We draw on ethnographic data collected between August 2015 and January 2017 at Columbia University and Barnard College. Our findings show that university training and an earnest desire to be responsible lead many men to intervene in possible sexual assaults. However, students' gendered methods target more socially vulnerable and socially distant men while protecting popular men and those to whom they are socially connected. Students' actual bystander practices thus reproduce social hierarchies in which low prestige may or may not be connected to actual risks of sexual assault. These results suggest that understanding intragroup dynamics and social hierarchies is essential to assault prevention in universities and that students' actions as bystanders may be effective at preventing assaults in some circumstances but may lead to new risks of sexual assault.